Of course the cops are racist: procedural justice, the perception of racial profiling, and citizen satisfaction with law enforcement - Lee, Jason (Criminology, criminal justice, law & society, 2017)
Racial profiling is typically treated in the academic literature as just one more null hypothesis to be tested. An area that has potentially greater impact, and that has been relatively neglected in the literature, is the perception among citizens that individual police officers engage in racial profiling. Using two waves of statewide survey data from 2003 and 2007, the current study examines the impact that the perception of racial profiling and attributions of procedural fairness and justice have upon citizen satisfaction with individual police officers. Binary logistic regression analysis revealed that the perception of racial profiling and broad attributions of procedural justice had a significant impact upon citizen perceptions of individual law enforcement officers, while more traditional indicators such as race, gender, and educational attainment failed to achieve statistical significance.